O casamento nas epístolas de São Jerônimo - Leite, Eduardo Silva (2013)
What was the conception of marriage of St. Jerome, which he did realize in his epistles? The relevance of the answer may be noticeable in a post-analysis of the historical path that ran through the wedding from the II to the fourth century. Considering the process of Christianization of Roman society, marriage, the end of the fourth century, received new "quality shots". For being a prominent Christian IV century, the voluminous works, with a considerable number of letters to the Roman families, thinking his conception of marriage is, at the same time, dwell on a universe of discourse that attempted to regulate the practices family relations in the late fourth century. Such evidence it is clear from these letters, a set of ascetic fervent speeches, addressed to Roman elites.